EVALUATION OF THE SUITABILITY OF GREEN OPEN SPACE LAND AGAINST MEDAN CITY SPATIAL PLANNING - Gusti Elcitra Limbong; Feby Milanie; Abdi Sugiarto (Bulletin of Engineering Science, Technology and Industry, 2024)
This study aims to evaluate the suitability of Green Open Space (RTH) land in Medan City based on the established Regional Spatial Plan (RTRW). Along with the rapid development of urbanization, land conversion, and increasing space needs in urban areas, Medan City faces challenges in maintaining and allocating RTH according to applicable standards. In this study, an analysis of land distribution in various sub-districts in Medan City was conducted to identify the suitability between the existing RTH area and the provisions of the RTRW. Data is processed using Geographic Information System (GIS) technology to produce accurate spatial visualization related to RTH allocation. The results of the study show that several sub-districts have green open space areas that are still below the standards set in the RTRW. Factors contributing to this mismatch include urbanization pressure, land conversion for industrial and residential purposes, and lack of supervision in the implementation of the RTRW. To address this problem, the study recommends strategies to increase green open space suitability through strengthening regulations, utilizing GIS technology for land monitoring, incentives for land owners, multi-sector collaboration, and adaptive RTRW revisions. With the implementation of this strategy, it is hoped that Medan City can improve the suitability of green open space according to the RTRW, which not only provides ecological benefits, but also supports sustainable urban development and improves the quality of life of the community.